Pelatihan Metode Geolistrik Untuk Mendukung Pembelajaran Teknik Eksplorasi Bawah Permukaan Kepada Siswa Kejuruan Geologi Pertambangan - Jaya, Gede Wiratma; Zulfiah; Ramadhan, Aditya; Bahri, Samsul; Rusmin, Yusril Jibran Rusady; Patty, Kayra Faith Love; Rivenia, Felisia Miselva; Melsano F. Nurue; Batlolona, Yohanis Toni; Sukri, Muh. Riswan Anas (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The province of Maluku has a rich potential of natural resources, particulary for metallic mineral such as gold and copper. To map this potential, human resources with competence in exploration engineering are needed. In 2017, SMK PGRI Ambon opened a new major in geological mining to prepare human resource who are ready to contribute to managing the mineral resources in Maluku Province. However, due to the lack of competence in subsurface exploration techniques, the Community Service team has partnered with SMK PGRI Ambon to support the competence of geological mining students in the field of subsurface exploration technique. This community service program uses the Service Learning method, which consists of several stages: 1) coordination, 2) activity preparation, 3) theoretical training on geoelectric method, 4) practical sessions on the geoelectrical method, and 5) evaluation of training results. The community service program was attended by 31 geological mining students from grades X to XII. The theoretical training and practical sessions on the geoelectric method were conducted on August 19-20, 2025. For the training session, the community service team provided theoretical material on the geoelectric method. For the practical session, students were taught how to use geoelectric equipment. Subsequently, they were also given material on processing geoelectric data and interpreting subsurface layers. The evaluation results indicate that the theoretical training on the geoelectric method successfully improved knowledge competence, with the average knowledge score increasing from 43.23 to 62.58. This community service activity has directly contributed to assisting SMK PGRI Ambon in providing knowledge and skills to its geological mining students.